Upper gastrointestinal bleeding: A rare complication of acute cholecystitis - Nana, Gael R. (Elsevier, 2013)
INTRODUCTION: Haemobilia is a rare complication of acute cholecystitis and may present as upper gastrointestinal bleeding. PRESENTATION OF CASE: We describe two patients with acute cholecystitis presenting with upper gastrointestinal bleeding due to haemobilia. Bleeding from the duodenal papilla was seen at endoscopy in one case but none in the other. CT demonstrated acute cholecystitis with a pseudoaneurysm of the cystic artery in both cases. Definitive control of intracholecystic bleeding was achieved in both cases by embolisation of the cystic artery. Both patients remain symptom free. One had subsequent laparoscopic cholecystostomy and the other no surgery. DISCUSSION: Pseudoaneurysms of the cystic artery are uncommon in the setting of acute cholecystitis. OGD and CT angiography play a key role in diagnosis. Transarterial embolisation (TAE) is effective in controlling bleeding. TAE followed by interval cholecystectomy remains the treatment of choice in surgically fit patients. CONCLUSION: We highlight an unusual cause of upper GI haemorrhage. Surgeons need to be aware of this rare complication of acute cholecystitis. Immediate non-surgical management in these cases proved to be safe and effective.